1997
DOI: 10.1038/sj.onc.1201343
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of genetic progression in human gastric carcinomas with microsatellite instability

Abstract: Mutator phenotype tumors provide unique opportunities to unravel malignant progression because of various gene alterations acquired during clonal tumor evolution. Gastric carcinomas, which have been known to show frequent genetic instability, would be composed of initial gene alterations shared by most tumor areas and subsequent alterations restricted to particular tumor sites. To analyse the timing of genetic events, we examined separate sites of tumor tissue obtained from a given gastric carcinoma patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
4
2

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 18 publications
10
60
4
2
Order By: Relevance
“…In four of the six tumours bearing BAX mutations, identical alterations in the [(G)8] tract were found in all sites sampled within each cancer, supporting the hypothesis that BAX mutation was present in the founder malignant clone. This pattern is also consistent with that described for BAX mutations in gastric cancers (Chung et al, 1997). However, in two of six cases we demonstrated a second pattern in which BAX mutation is not shared by all the tumour sites of the same cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In four of the six tumours bearing BAX mutations, identical alterations in the [(G)8] tract were found in all sites sampled within each cancer, supporting the hypothesis that BAX mutation was present in the founder malignant clone. This pattern is also consistent with that described for BAX mutations in gastric cancers (Chung et al, 1997). However, in two of six cases we demonstrated a second pattern in which BAX mutation is not shared by all the tumour sites of the same cancer.…”
Section: Discussionsupporting
confidence: 92%
“…These observations strongly suggest that microsatellite instability is acquired at the adenoma-carcinoma interface in the evolution of sporadic tumours, but can appear at an Cae=caecum, asc=ascending colon, sig=sigmoid colon, mucoid=mucoid carcinoma, ac md=moderately di erentiated adenocarcinoma, ac pd=poorly di erentiated adenocarcinoma, ac/mu=mixed adenocarcinoma glandular/mucoid pattern, +(loss)=deletion of one G from the [(G)8] tract, +(gain)=insertion of one G in the [(G)8] tract earlier stage in patients who carry germline mutations in MMR genes. Previous studies have shown clonal expansion of shifts of di erent amplitude at the same microsatellite locus sampled from di erent sites in the same tumour (Chung et al, 1997), as observed in the present work also. This indicates that a proportion of these microsatellite mutations are acquired as clonal variants throughout the process of tumour formation and re¯ect but do not cause the evolution of such tumours.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of a mutator phenotype, similar to that observed in Hereditary Non-Polyposis Colon Cancer (HNPCC) and gastric carcinomas was investigated by searching for frameshift mutations in TGF-b type IIR and Bax. Mutations in polypurine tracts within these genes have been reported in human tumours, such as gastric carcinoma, with MSI Parsons et al, 1995;Chung et al, 1997). However, the absence of any such changes in the BRCA-associated tumours in the present series implies that a classical mutator phenotype is not present in BRCA-associated tumours.…”
Section: Discussioncontrasting
confidence: 63%
“…The presence of sequence changes in a 268 bp fragment of b-globin was tested by SSCP using PCR conditions previously described (Bauer et al, 1991). Analysis for the presence of MSI-associated frameshift mutations in the coding regions of TGF bRII [poly(A) 10 ] tract and Bax [poly(G) 8 ] tract was performed as described previously by Chung et al (1997).…”
Section: Analysis Of Gene Sequencementioning
confidence: 99%
“…This genetic model is also supported by other indications. By analyzing separate tumor areas from a small number of MMP ϩ gastric carcinomas, Chung et al reported a progressive accumulation of mutations, beginning with frameshifts in TGF␤RII and BAX followed by lesions in hMSH3 and hMSH6 and, as a last step, by mutations in IGFIIR (Chung et al, 1997). TGF␤RII mutations were found during the transition from colon adenoma to carcinoma, earlier than any other reported CDRs MSI (Grady et al, 1998).…”
Section: Discussionmentioning
confidence: 99%